How Does Financial Accountability, Information Quality, and Altruism Drive Business Zakat Compliance Through Business Growth Mediation? - Pakawaru, Irham; Muhammad Syafaat (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2023)
This study aims to address knowledge gaps through a holistic approach, considering individual and organizational factors in the context of business zakat compliance. It involves financial accountability, information quality, and altruism as relevant factors, with information quality and altruism being mediated by business growth. Data were collected through questionnaires from 100 Small and Medium Enterprises in Palu City, Donggala Regency, and Sigi Regency, using purposive sampling. The analysis employed SEM PLS methodology. Findings indicate no significant support for the relationship between financial accountability and business growth. Conversely, information quality and altruism exhibit significant relationships. In the context of business zakat compliance, no relationships were found between financial accountability, information quality, and altruism. However, the relationship between business growth and zakat compliance proved to be significant. Mediation analysis revealed that only the relationships between information quality, altruism, and zakat compliance are mediated by business growth, while the relationship between financial accountability and zakat compliance is not mediated. Study limitations include specific context, reliance on cross-sectional data, and a narrow focus on SMEs in a specific industry. Future research recommendations encompass longitudinal studies, sample expansion, and exploration of the cultural and technological impacts on financial practices and compliance